2019
DOI: 10.37358/rc.19.11.7716
|View full text |Cite
|
Sign up to set email alerts
|

Improving the Mechanical Behavior of a Helicopter Tail Rotor Blade Through the Use of Polyurethane Foams

Abstract: The tail rotor blade represents a very important component in the structure of any helicopter, being subjected to many aerodynamic loads. The integrity of this component is essential for maintaining flight safety and improving its characteristics can increase the overall performance of the helicopter. Thus, in some cases, some improvements can be made to the structure, in order to reduce the weight of the component and to improve its mechanical properties and its reliability in flight. The current paper presen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 1 publication
0
6
0
Order By: Relevance
“…helicopter tail rotor blade [6] The main material properties of the IAR330 metal tail rotor blade components are presented in Table 1. Taking into consideration the abundent development of composite and polymeric materials designed to satisfy requirements from various domains, the material selection for a composite tail rotor blade has to be realised with respect to the vibrational response of the structure.…”
Section: Figure 1 Main Structural Elements Of the Iar330mentioning
confidence: 99%
See 1 more Smart Citation
“…helicopter tail rotor blade [6] The main material properties of the IAR330 metal tail rotor blade components are presented in Table 1. Taking into consideration the abundent development of composite and polymeric materials designed to satisfy requirements from various domains, the material selection for a composite tail rotor blade has to be realised with respect to the vibrational response of the structure.…”
Section: Figure 1 Main Structural Elements Of the Iar330mentioning
confidence: 99%
“…A previous attempt to define structural behavior similarities between a honeycomb aluminium alloy core and a full metal core has been done for the IAR330 tail rotor blade model [6]. The finite element study concluded with a comparison of static structural numerical analysis results, highlighting the https://doi.org/10.37358/MP.20.2.5363 posibility of replacing the honeycomb core with a full inner core, in order to achieve a more convenient processing time for the numerical analysis, while determining similar results.…”
Section: Figure 1 Main Structural Elements Of the Iar330mentioning
confidence: 99%
“…Composite materials have been wildly applied to many engineering aspects, such as marine machines, aerospace, vehicles, and airplanes because of its good mechanical properties, corrosion resistance, fatigue durability, and tribological properties 1,2 . In addition, many materials commonly used in industry, such as natural rubber, polypropylene (PE), high density polyethylene (HDPE), thermoplastic polyurethanes (TPU), and ultra‐high molecular weight polyethylene (UHMWPE) exhibit excellent self‐lubricating properties and have been used to manufacture key moving components, such as the marine water‐lubricated stern bearings, the nuclear bearings, helicopter bearings and aircraft bearings 3–10 . Owing to their special working environment, polymer bearings are subjected to the multifaceted effects of alternating stresses originating from the external environment and gravity, which obviously generate friction and vibration 11 .…”
Section: Introductionmentioning
confidence: 99%
“…Several studies related with blast attenuation applications pointed out that the energy dissipation process is closely related with the material volumetric strain capacity [5][6][7][8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%